XRD, HRTEM, magnetic, dielectric and enhanced microwave reflection loss of GaFeO3 nanoparticles encapsulated in multi-walled carbon nanotubes. Issue 3 (15th February 2016) - Mahapatra, A.S.; Mitra, A.; Mallick, A.; Chakrabarti, P.K.
Abstract: Nanoparticles of GaFeO3 are prepared by a sol–gel method where ultrasonication is used to reduce the distribution of sizes and agglomeration among nanoparticles. To obtain the well crystallographic phase, the as prepared sample is annealed at 800 °C for 6 h. To explore the applications in the field of microwave devices, multiferroic nanoparticles of GaFeO3 are incorporated in multi-walled carbon nanotubes (MW-CNTs). The formations of the desired crystallographic phases of both the bare and encapsulated samples are confirmed by X-ray diffractograms. Results of high resolution transmission electron microscopy of the coated sample confirm the encapsulation of nanoparticles of GaFeO3 in the matrix of MW-CNTs. Raman spectra are recorded at room temperature and the observed spectra are analyzed to extract different informations like the presence of any impurity, position of different Raman active modes, shift of Raman peak etc. of the sample. The reflection loss of the bare and coated samples in the X and Ku bands of microwave regions (8–12 GHz and 12–18 GHz) are measured and interestingly, the microwave reflection loss is significantly enhanced due to encapsulation of GaFeO3 by MW-CNTs. This enhancement will improve the quality of applications of GaFeO3 in microwave devices.